Mekanisme Perlindungan Hukum bagi Pihak dalam Perikatan Kredit Perbankan - Maman Nurohman; Muhammad Luthfi Saputra; Shinta Putri Sanjaya; Zheea Keisha Rahmandita (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
Based on Article 1313 of the Civil Code, which states that an agreement is an act in which one or more people bind themselves to one or more other people. In the research we conducted, there were problems that were still widespread regarding banking credit agreement issues that had not yet been resolved. So in the research we conducted we discussed the protection mechanisms in banking credit agreements against cases of default that occur in banking credit agreements. The research we use is normative research, where in this research we delve more deeply into secondary information in the form of literature reviews and related laws and regulations. Banking credit agreements involve customers as debtors and banks as creditors. Legal protection in this agreement is regulated by various laws and regulations which regulate the rights and obligations of both parties, dispute resolution mechanisms, as well as preventing abuse of authority or default. The purpose of making a bank credit agreement in written form is to guarantee proof of the existence of the agreement if one of the parties breaks a promise or defaults, as well as guaranteeing legal certainty for both creditors and debtors.